2008
DOI: 10.21608/absb.2008.8335
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Dipyridylketone With Group 8 Metal Carbonyls in Different Media

Abstract: Reaction of di-(2-pyridyl)ketone (dpk) with [M 3 (CO) 12 ], M =Ru or Os in dioxan under reduced pressure gave the tricarbonyl derivative [Ru(CO) 3 (dpk)] (1) and [Os(CO) 3 (dpk)] (2). When these reactions were carried out in benzene/ethanol 1:1 (v:v) under reflux and reduced pressure gave the binuclear ruthenium complex [Ru 2 (CO) 4 (-CO)( 3 -dpkO,Oeth) 2 ] (3), where  3 -dpkO,Oeth is N,O,N-ethoxybis(2-pyridyl)-methanolato and the mononuclear [Os(CO) 3 ( 3 -dpkO,Oeth) (4). All complexes were characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Almost identical adherence was reported in a study conducted by Venkatachalam et al (24%) in India but was higher in other studies reported from Malaysia (44%) and Egypt (72%) which could be due to different socio demographic profile. 3,20,21 While a community based study also showed a prevalence of 59%. 17 In our study, adherence was higher among people in the age group above 60 years (24.5%), females (28%) compared to males and among married (26.9%) than widow/er.…”
Section: Discussionmentioning
confidence: 99%
“…Almost identical adherence was reported in a study conducted by Venkatachalam et al (24%) in India but was higher in other studies reported from Malaysia (44%) and Egypt (72%) which could be due to different socio demographic profile. 3,20,21 While a community based study also showed a prevalence of 59%. 17 In our study, adherence was higher among people in the age group above 60 years (24.5%), females (28%) compared to males and among married (26.9%) than widow/er.…”
Section: Discussionmentioning
confidence: 99%